Knowledge of NFPE-AG graduates on reproductive health and nutrition - Ali, Ahmed; Mahmud, Shah Noor; Karim, Fazlul; Islam, Md. Nazrul; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2019)
BRAC educated adolescent girls through its Non-Fonnal Primary Education Programme for Adolescent Girls (NFPE-AG) as a component of its fonner Women's Heath and Development Programme (WliDP). The aim of the NFPE-AG programme was to increase the literacy and numeracy skills . as well as awareness on reproductive health, nutrition and social isSues~ The first phase ofNFPE-AG was started in September 1991 through 1000 schools in 10 thanas of WHDP and ended in August 1993. 1bis study was undertaken to assess the level of knowledge retained by NFPE-AG graduates regarding reproductive health and nutrition issues such as marriage, pregnancy, safe motherhood and contraception, delivecy, lactation, anaemia, goitre and menstruation. A total of 30 former ~"FPE-AG schools (closed 2 years back) were selected from 6 WHDP areas (5 schools from each area). From each schoo~ 7 NFPE-AG graduates aged 15-19 years were selected who did not continue their study in fonnal schools after graduation. Another 7 never schooling girls (NS-AGs) aged 15-19 years from TG families were selected as a comparison group. Thus, a total of 420 adolescent girls (210 from each group) were interviewed in January 1996.